The role of assistance dogs in society - Audrestch, Hilary M.; Whelan, Chantelle T.; Grice, David; Asher, Lucy; England, Gary C.W.; Freeman, S.L. (Elsevier, 2015)
Assistance dogs are specially trained to undertake a variety of tasks to help individuals with disabilities. This review gives an overview of the different types of assistance dogs in the UK, including guide dogs, hearing dogs, mobility assistance dogs, service dogs and dual purpose dogs. The literature describes many benefits of assistance dogs, including their impact on physical wellbeing and safety of their ‘owners,’ as well as on psychological wellbeing and social inclusion. The role of assistance dogs in society is widely recognized by the public, but is not currently acknowledged in government social policy. The current evidence on the benefits of assistance dogs is limited by the type and scale of current research. This article highlights the need for independent funding for high quality research to enable social care and policy makers to make evidence-based decisions on the value of assistance dogs to people with disabilities.